Factors impacting the access and use of formal health and social services by caregivers of stroke survivors: an interpretive description study - Anna Garnett; Jenny Ploeg; Maureen Markle-Reid; Patricia H. Strachan (BMC, 2022)
Abstract Background Evidence has shown that family and friend caregivers of stroke survivors are significantly and negatively impacted by caregiving. The negative effects of caregiving may persist over time suggesting that caregivers might benefit from ongoing engagement with supportive services. However, little is known about caregivers' use of formally funded health and social services, or the factors influencing their access to and use of these services. The aim of this study is to increase understanding of the factors that influence stroke caregivers' access and use of formal health and social services, from the perspective of stroke caregivers and healthcare providers. Methods A qualitative study was conducted with stroke caregivers and health providers in Ontario, Canada using interpretive description. In-depth interviews were conducted with caregivers of survivors who experienced a stroke between six months to five years previous and healthcare providers who support caregivers and stroke survivors. All participants provided written informed consent. Interview data were analyzed using constant comparison to identify codes and develop key thematic constructs. Results A total of 40 interviews were conducted with 22 stroke caregivers at an average 30-months post-stroke and 18 health providers. Factors that influenced stroke caregivers' access and use of services included: finances and transportation; challenges caregivers faced in caring for their health; trust that they could leave their family member and trust in health providers; limited information pertaining to services and a lack of suitable services; and the response of their social networks to their caregiving situation. Conclusion Stroke caregivers experience significant challenges in accessing and using formal health and social services. These challenges could be addressed by increasing availability of subsidized community-based supports such as respite and counselling tailored to meet the ongoing needs of caregivers. Systemic change is needed by the health system that readily includes and supports caregivers throughout the stroke recovery continuum, particularly in the community setting.